Towards Anthony Paul Smith, A Non-Philosophical Theory of Nature: Ecologies of Thought - Kolozova, Katerina (Identities: Journal for Politics, Gender and Culture, 2013)
Author(s): Katerina Kolozova Title (English): Towards Anthony Paul Smith, A Non-Philosophical Theory of Nature: Ecologies of Thought Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 136-137 Page Count: 2 Citation (English): Katerina Kolozova, “Towards Anthony Paul Smith, A Non-Philosophical Theory of Nature: Ecologies of Thought,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 136-137.